Building Real World Cloud Apps with Windows Azure - Dykstra, Tom (Microsoft, 2014)
This e-book walks you through a patterns-based approach to building real-world cloud solutions. The patterns apply to the development process as well as to architecture and coding practices. The content is based on a presentation developed by Scott Guthrie and originally delivered at the Norwegian Developers Conference (NDC) in June of 2013. Many others updated and augmented the content while transitioning it from video to written form.